Islam, empire of faith [videorecording (DVD)] - Gardner, Robert A.; Kingsley, Ben, 1943- (Empires, 2005)
Documents the rise and growth of Islam throughout the world, from the birth of Prophet Muhammad in the 6th century through the peak of the Ottoman Empire 1000 years later. Discusses the impact of Islamic civilization on world history and culture.